Clinical relevance of non-tuberculous mycobacteria isolated in the Nijmegen-Arnhem region, The Netherlands. Issue 6 (12th February 2009) - van Ingen, J; Bendien, S A; de Lange, W C M; Hoefsloot, W; Dekhuijzen, P N R; Boeree, M J; van Soolingen, D
Abstract : Background: The frequency of clinical isolation of non-tuberculous mycobacteria (NTM) in the Netherlands is increasing, but its clinical relevance is often uncertain. Objective: To assess the frequency and clinical relevance of isolation of NTM in four associated hospitals in a single region in the Netherlands. Methods: Medical files of all patients from whom NTM were isolated between January 1999 and January 2005 were reviewed retrospectively. Diagnostic criteria for non-tuberculous mycobacterial disease published by the American Thoracic Society (ATS) were used to determine clinical relevance. Results: 232 patients were found, from whom NTM were isolated from the respiratory tract in 91% of cases. Patients were mostly white men, with an average age of 60 years and pre-existing pulmonary disease. Fifty-three of 212 patients (25%) with pulmonary isolates met the ATS diagnostic criteria for pulmonary NTM disease; this percentage differed by species. Most patients were treated with rifampicin, ethambutol and clarithromycin. Treatment outcome for pulmonary NTM disease was suboptimal but differed by species: overall, improvement was seen in 67% of treated patients, but in only 50% of those with pulmonary M avium disease. Lymphadenitis was the most common extrapulmonary disease type. Conclusions: Twenty-five per cent of all patients with pulmonary NTM isolates met the ATS criteria. Clinical relevance differs by species. NTM isolation increases over time. Species distribution differs from that of neighbouring countries and the M avium complex isolates have traits different from those reported in the USA. Adherence to diagnostic and treatment guidelines can be improved.